Effect of Patients’ Life Stories in Bringing Meaning to Nursing Home Care - Qu, Jane (PRiMER, 2019)
INTRODUCTION: Although there is an increasing need for geriatricians, fewer physicians are entering the field. Family medicine residents find geriatrics, especially nursing home care, unsatisfying. Life stories of older adult patients may help providers cope with the challenges of nursing home care and increase provider satisfaction by offering a way to connect with patients. METHODS: We conducted a qualitative study on life stories’ effects on attitudes towards nursing home care. Fourteen patient stories were created. Seven Boston University family medicine residents and one nurse practitioner participated in a semistructured interview both before and at least 2 months after learning about their patients’ stories. Data were analyzed using qualitative techniques from grounded theory. RESULTS: Participants found nursing home care challenging, particularly for patients who were nonverbal due to advanced dementia, because they had difficulties forming meaningful relationships or discussing medical decisions with their patients. Life stories increased empathy, deepened relationships with patients, and led participants to feel more satisfied in their role as providers. The stories were considered useful for end-of-life discussions. CONCLUSION: Life stories incorporated into physician practice may help health care providers feel more connected to their patients and ultimately more satisfied in the care of nursing home patients.